Untersuchungen über die Wirkung verschiedener Substanzen als Lock- oder Fraßstoff auf einige Insektenarten (Vorläufige Mitteilung). - Gottschalk, Cord (Contributions to Entomology = Beiträge zur Entomologie, 1957)
1. Until now it was not possible to find out in experiments an attractive specifical for Musca domestica L. respectively Fannia canicularis L. - 2. Leptinotarsa, decemlineata L. preferred baits infiltrated with cane-sugar solution above a solution treated with aqueous acetaldehyd. Galaktosebaits were not infested. It seems that Leptinotarsa decemlineata L. breaked in geraniol preferred at least in the beginning this odour above the odour of potato leaves. - 3. Melolontha vulgaris L. infested the leaves of different plants, included herbaceous plants. Usually a solution of tannin respectively a solution of wettable cane-sugar intensified the feeding.